Drug abuse sourcebook : basic consumer health information about the abuse of cocaine, club drugs, marijuana, inhalants, heroin, hallucinogens, and other illicit substances and the misuse of prescription and over-the-counter medications : along with facts and statistics about drug use and addiction, treatment and recovery, drug testing, marijuana as medicine, drug abuse prevention and intervention, glossaries of related terms, and directories of resources for additional help and information - Larsen, Laura (Detroit, MI : Omnigraphics, 2016)
"Provides basic consumer health information about the abuse of illegal drugs and misuse of prescription and over-the-counter medications, along with facts about causes and consequences of drug abuse, prevention, treatment, and recovery. Includes index, glossary of related terms and directory of resources"--
Part I: facts and statistics about drug abuse in the United States -- Part II: drug abuse and specific populations -- Part III: drugs of abuse -- Part IV: the causes and consequences of drug abuse and addiction -- Drug abuse treatment and recovery -- Part VI: drug abuse testing and prevention -- Part VII: additional help and information.
Revised edition of Drug abuse sourcebook, 2014.
Includes bibliographical references and index.
Keywords: Drug abuse -- Prevention -- Handbooks, manuals, etc; Drug abuse -- Treatment -- Handbooks, manuals, etc; Drug addiction -- Treatment -- Handbooks, manuals, etc; Handbooks and manuals